Proceedings of the Annual Civic Education Conference (ACEC 2018) 2018
DOI: 10.2991/acec-18.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Quotient, Family Environment and Their Influences on Teacher Performance

Abstract: This study aims to examine the problem of teacher performance weakness by studying emotional quotient and family environment, and its positive influence on teacher performance. The data was collected through questionnaire from 61 teachers and 183 students, which selected by multistage sampling technique. The data were analyzed descriptively and inferentially with multiple regression and correlation analysis. The result showed that: (1) emotional quotient has a positive effect on teacher's performance, (2) reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
2
Order By: Relevance
“…Strengthening the emotional intelligence of madrasah teachers will make teaching professionalism and mastery of teaching students higher. The results of Lonto, Pasandaran & Pangalila (2018) study revealed that social-emotional learning is part of emotional intelligence, which in practice is another way to focus on the measurement and remediation of individual deficits rather than a way to redirect educators' focus to the context of classrooms and school relationships. However, social, emotional learning guarantees to foster increased achievement and equity in education may not be realized unless there is more work to bed one to connect ideals with practices and address the political and cultural assumptions built into contemporary approaches.…”
Section: The Influence Of Islamic Psychosocial On Learning Assessment Of Madrasah Aliyah Teachersmentioning
confidence: 99%
“…Strengthening the emotional intelligence of madrasah teachers will make teaching professionalism and mastery of teaching students higher. The results of Lonto, Pasandaran & Pangalila (2018) study revealed that social-emotional learning is part of emotional intelligence, which in practice is another way to focus on the measurement and remediation of individual deficits rather than a way to redirect educators' focus to the context of classrooms and school relationships. However, social, emotional learning guarantees to foster increased achievement and equity in education may not be realized unless there is more work to bed one to connect ideals with practices and address the political and cultural assumptions built into contemporary approaches.…”
Section: The Influence Of Islamic Psychosocial On Learning Assessment Of Madrasah Aliyah Teachersmentioning
confidence: 99%
“…However, a study conducted by Consemino (2011) found out that there was no significant relationship between performing school administrators and their work attitude. On the other hand, emotional quotient has positive effect on teacher performance, according to Lonto et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor worth considering is the effect of family environment on teachers' performance, which is another facet of the emotional capabilities in the profession (Lonto, et al, 2018). To further prove the essence of emotional quotient to teacher's efficacy, Shafiq and Rana (2016) concluded that teachers' environment at home reflects a reasonable power of predictability toward the organizational commitment of teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Suyanto ( 2009) dalam (Lonto & Pangalila, 2013), karakter merupakan cirri khas tiap individu dan cara berfikir untuk hidup dan bekerja sama serta berperilaku yang baik sehingga dapat membuat keputusan bahkan sikap mempertanggungjawabkan tiap keputuasan yang diperbuat.…”
Section: Susanto (2008) Dalam Irfan Adiunclassified